Stakeholder-Based Risk Analysis in Post-Disaster Housing Projects: Toward Improved Risk Management Practices - Malahayati, Nurul; Munirwansyah; Syamsidik (Civil Engineering Journal, 2026)
Reconstructing housing after a disaster is a demanding and intricate process, particularly when managing risks that affect project delivery timelines. The community-based approach, widely adopted in Indonesia, seeks to foster local participation but is often hindered by implementation challenges. This study aims to identify and analyse the critical risks contributing to delays in community-driven housing reconstruction projects in Pidie Jaya Regency, Aceh, Indonesia, as perceived by stakeholders. Research variables were developed sequentially through a literature review, semi-structured interviews, focus group discussions (FGDs), and questionnaires. A mixed-methods approach was employed, combining thematic analysis with descriptive statistics and indices, such as the frequency index (FI), severity index (SI), and risk importance index (RII). Seventy-one risk variables were identified, including 17 newly documented risks not previously addressed in the literature. Three variables were found to be particularly significant: shortage of facilitators, limited labour availability, and insufficient community construction skills. The findings contribute theoretically by broadening the understanding of operational risks during the construction phase and offer practical guidance for policymakers in developing more effective mitigation strategies, with implications for other developing nations utilising community-based reconstruction.